Efektifitas Strategi Pengendalian Wake-effect dalam Memaksimalkan Produksi Daya Ladang Turbin Angin - Kurniawan; Hasanudin; Dwiyanto, Agus; Tyaksa Putra, Rivanda (Institut Teknologi Nasional Yogyakarta, 2024)
The wake effect is an aerodynamic interaction between turbines in a wind farm, where wind flow is blocked by turbines ahead, leading to a total power loss of 10-25%. The wake effect can be controlled by adjusting the yaw-offset angle, pitch angle, tip-speed ratio, or a combination of these strategies. This research aims to compare and determine the most effective control strategy to maximize total wind farm power production. The method involves analyzing and simulating various control strategies to reduce the wake effect. A Gaussian wake-effect model is used to simulate wind flow patterns, turbine interactions, and total wind farm power. Data is generated from simulations under wind speeds of 3 m/s and 10 m/s, and turbine spacing of 7D and 12D. Results show that total wind farm power production increased by 11.41%, 2.21%, 0.00%, and 12.70% for yaw-offset angle, pitch angle, tip-speed ratio, and a combination of the three, respectively. The study identifies the combination of these parameters as the most effective strategy for reducing the wake effect. Proper wake-effect control can significantly boost total wind farm power production, with broader potential applications for commercial wind farms in the future.